Unstructured electrical impedance tomography using ad hoc sensor node - Abbas Ibrahim Mbulwa (2019)
Electrical Impedance Tomography (EIT) is a simple solution for obtaining information about the interior of an object or a process through performing voltage measurements, whereby interior conductivity distribution in an object can be reconstructed in a form of tomograms. EIT has many applications in areas such as medical, geophysical, and industrial process, where it has shown various potential over existing tomographic modalities. However, the main drawback has been low spatial resolution towards the center of the object. The objective of this project is to obtain EIT measurements from the interior of the object under test, through the employment of ad hoe internal electrodes, in an effort to acquire data that were unobtainable through conventional EIT system. To achieve this objective, a prototype of an ad hoe EIT sensor is designed. The ad hoe EIT sensor is battery powered. The sensor node is attached with two pairs of electrodes. The sensor integrated circuit is designed to enable current injection and voltage measurement from within the medium using the two pairs of electrodes. One pair performs current injection, while another pair measures localized voltage difference. The role of the two pairs are interchangeable by using analog multiplexers. The sensor integrated system consisting of a current source, voltage sense, multiplexers, and microcontroller unit, were simulated and tested. The ad hoe sensor prototype was experimented on homogeneous medium and inhomogeneous medium of tap water and saline. The results show a feasible means of acquiring EIT data from the interior of the object.